The New Uranium Mining Boom Challenge and Lessons learned - Merkel, Broder; Schipek, Mandy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The book presents the results from the Uranium Mining and Hydrogeology Conference (UMH VI) held in September 2011, in Freiberg, Germany. The following subjects are dealt with in depth: uranium mining, phosphate mining and uranium recovery. Cleaning up technologies for water and soil are also discussed at length. Analystics and sensors for uranium and radon and modelling round up this comprehensive volume.
Plenary -- Renaissance of Uranium Mining -- Phosphate Mining and Uranium recovery -- Cleaning up technologies for water and soil -- Analytics and Sensors for Uranium and Radon -- Modelling -- Miscellaneous.
Keywords: Geography; Hydraulic engineering; Mines and mineral resources; Earth Sciences; Mineral Resources; Hydrogeology